Decarbonization Strategy and Sustainable Competitive Advantage: Multi-Criteria Analysis and Transformation Roadmap for PT. SET - Purwanto, Yuli; Purwanto, Agustinus HD (Journal of Sustainable Economic and Business, 2026)
Objectives: This study aims to formulate an effective decarbonization strategy and roadmap for PT. SET in responding to global regulatory pressures, specifically related to reducing the Carbon Intensity Indicator (CII) for its fleet. The research focus is to identify the most feasible strategic options to improve the CII Rating to level B within 2-3 years.Methodology: The research uses an explanatory sequential mixed methods approach with a single case study design. Data was collected through in-depth interviews, discussions, Focus Group Discussions (FGD) with management, and documentation studies. Analysis was conducted sequentially using the PESTEL framework, Porter's Five Forces, SWOT, Gap Analysis, Fishbone Diagram, and Multi-Criteria Decision Analysis (MCDA) to evaluate decarbonization solution options.Finding: The research results indicate that two of SET's four main vessels (Sinar MDLK and Sinar MSL) are at risk of reaching CII Rating E by 2025. The MCDA analysis ranked Voyage Optimization & Voyage Management System (VMS) as the best option (score 4.80) due to its direct impact on fuel savings (10–20%), fast payback period (<1 year), and its function as a digital foundation for long-term transformation.Conclusion: Strategic recommendations include VMS implementation, an exit strategy for old vessels, and acquisition of second-hand vessels that are already digitalized. The 2026–2030 decarbonization roadmap is designed in five phases not only to achieve the target CII Rating B by 2028 and ensure compliance but further to transform regulatory pressure into a foundation for sustainable competitive advantage, with digital transformation as its main driver.